(untitled) (International Journal of Scientific Research in Science and Technology, 2025)
Handwriting is a highly complex motor skill that has long fascinated researchers and forensic experts alike. This study investigates how writing speed affects handwriting after an individual reaches’ graphic maturity. Graphic maturity refers to the stage where handwriting becomes a mostly automatic process, requiring minimal conscious effort. The research involved collecting handwriting samples from individuals across different age groups, written at varying speeds. These samples were then examined to identify changes in both class characteristics (e.g., slant, spacing, size) and individual characteristics (e.g., specific strokes, pressure, unique formations). The analysis revealed that speed significantly influences handwriting features. In many cases, increased writing speed led to noticeable alterations in class characteristics, which in turn affected the visibility and stability of individual characteristics. One of the key findings is that these shifts can actually help forensic experts isolate unique traits specific to the writer, enhancing the accuracy of forensic handwriting analysis. A visual representation of these changes helped simplify complex data, making it more accessible for practical application. This study contributes to forensic science by providing deeper insight into how writing speed influences handwriting features, aiding the identification and verification process in criminal and civil cases.